Evaluation of the utility of early routine computed tomography angiography in subarachnoid hemorrhage patient outcomes. (July 2021) - Ascanio, Luis C.; Dmytriw, Adam A.; Chida, Kohei; Enriquez-Marulanda, Alejandro; Mayeku, Julie; Gupta, Raghav; Maragkos, Georgios; Alturki, Abdulrahman Y.; Darbaz, Berkan; Thomas, Ajith J.; Ogilvy, Christopher S.; Moore, Justin M.
Highlights: Early CTA refers to CTA performed between days 5–8 post-SAH in stable patients. Early CTA was independently associated with lower poor outcomes at discharge. Vasospasm presence on early CTA was associated with a higher risk of poor outcomes. Early CTA was not associated with outcomes at clinical follow-up. Abstract: Objectives: The role of an early CTA approach in neurologically stable patients with nontraumatic SAH has not been assessed. This study explored the use of CTA in clinically stable SAH patients to pre-emptively identify cerebral vasospasm, to evaluate whether this approach is associated with improved clinical outcomes. Methods: We conducted a retrospective chart review of SAH patients presenting between July 2007 and December 2016 in a single academic center. Patients were divided into two groups: (1) Early CTA (stable patients who underwent a CTA between days 5–8 post-SAH), and (2) Standard Protocol. The co-primary outcomes were a composite of the mRS at discharge and last clinical follow-up (good = 0–2; poor = 3–6). A multivariable binary logistic regression was conducted to compare both groups against outcomes, controlling for potential confounders. Results: A total of 415 patients were included, 103 (24.8%) with early CTA, and 312 (75.2%) undergoing the standard protocol; the mean age was 57 years and 248 (59.8%) patients were female. Patients in the early CTA group had a higher modified Fisher grade (3–4) (87.4% vs 63.1%; p < 0.02). The multivariable analysis showed that early CTA was independently associated with lower poor outcomes at discharge (OR = 0.21, 95% CI 0.07–0.61, p = 0.004). Plus, vasospasm detection was associated with an increased risk of poor outcomes (OR = 4.77, 95% CI 1.41 – 16.10, p = 0.01). Early CTA was not associated with outcomes at clinical follow-up. Conclusion: The early CTA surveillance approach was associated with better functional outcomes at discharge when compared to the current imaging standard practice.